Anisotropy of the Electrocaloric Effect in Lead‐Free Relaxor Ferroelectrics. Issue 9 (20th March 2014) - Goupil, Florian Le; Axelsson, Anna‐Karin; Dunne, Lawrence J.; Valant, Matjaz; Manos, George; Lukasiewicz, Tadeusz; Dec, Jan; Berenov, Andrey; Alford, Neil McN.
<x xml:space="preserve">Abstract</x> The highly anisotropic electrocaloric effect, evidenced by both direct measurements and a descriptive theoretical model in lead‐free relaxor ferroelectric Sr0.75Ba0.25Nb2O6 single crystals, can be exploited by producing low‐cost grain‐oriented ceramics. Combined with the broad‐temperature‐range cooling regime provided by their polar nanoregions, these materials may be the key to future cost‐ and energy‐efficient solid‐state refrigeration. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>